2014
DOI: 10.2116/analsci.30.691
|View full text |Cite
|
Sign up to set email alerts
|

Stability Study of the Antihistamine Drug Azelastine HCl along with a Kinetic Investigation and the Identification of New Degradation Products

Abstract: The first stability-indicating HPLC method was developed and validated for azelastine HCl (AZL). The separation of AZL from its degradation products was achieved on a C18 column using acetonitrile-0.04 M phosphate buffer of pH 3.5 (32:68, v/v) as a mobile phase with UV-detection at 210 nm and naftazone as an internal standard. The method was rectilinear over the range of 0.2 -20.0 μg mL -1 with a detection limit of 7.05 ng mL -1 . The degradation behavior of AZL was studied under different ICH-recommended stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 7 publications
(10 reference statements)
0
22
0
Order By: Relevance
“…From an economic point of view, the proposed method seems to be so simple, sensitive and fast. Scheme is the expected proposal for the degradation of AZL, as illustrated by Rania et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From an economic point of view, the proposed method seems to be so simple, sensitive and fast. Scheme is the expected proposal for the degradation of AZL, as illustrated by Rania et al .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, our method is one of the most sensitive reported for the determination of AZL, permitting determination of the drug at the ng level and facilitating its quantitation in metered dose nasal sprays. The proposed method has been found to be ~20–50 times more sensitive than the previously reported method ; in addition, the proposed method does not require complicated set‐up, unlike another method reported in the literature that needs a sophisticated LC–MS instrument .…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Reviewing the literature revealed that different analytical methods were established for determination of FLP and AZH either alone or in combination. These methods include: spectrophotometry [5][6][7][8][9][10][11][12], spectrofluorometry [13,14], electrochemical methods [15][16][17], TLC [18,19], HPLC [5,11,[20][21][22][23][24][25][26][27][28][29]] HPTLC [30][31][32], LC/MS/MS [33][34][35][36][37][38][39] and capillary electrophoresis [40,41]. It was found that only two spectrophotometric methods [42,43] and two HPLC methods [44,45] were reported for quantification of the binary mixture of FLP and AZH.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, various chromatographic methods have been published for estimation of AZL, including high‐pressure thin‐layer chromatography (Dubey, Das, Roychowdhury, Pradhan, & Ghosh, ; Kumar, Dwivedi, Kushnoor, & Kushnoor, ; Salama, Abdel‐razeq, Abdel‐atty, & El‐kosy, ; Sane, Joshi, Francis, Khatri, & Hijli, ; Wyszomirska, Czerwińska, Kublin, & Mazurek, ), capillary electrophoresis (CE; Koppenhoefer, Epperlein, Xiaofeng, & Bingcheng, ; Koppenhoefer, Jakob, Zhu, & Lin, ; Suzuki, Ishihama, Kajima, & Asakawa, ), HPLC (EL‐Shaheny & Yamada, ; Rao et al, ; Thangabalan & Kumar, ) and LC/MS (Heinemann, Blaschke, & Knebel, ; Park et al, ; Zha & Shum, ). All of these published methods, are not concerned with resolution and determination of AZL in presence of both BC and AZL genotoxic impurity.…”
Section: Introductionmentioning
confidence: 99%